Right ventricular myocardial work in patients undergoing left ventricular assist device implant. (3rd October 2022) - Mandoli, G E; Landra, F; Pica, A; Marrese, F; Gallone, G; Sciaccaluga, C; Cavigli, L; D'Ascenzi, F; Focardi, M; Maccherini, M; Bernazzali, S; Valente, S; et al.
Abstract: Background: Right ventricular failure (RVF) complicates 10 to 40% of left ventricular assist device (LVAD) implants, with necessity of high dose inotropic/vasodilatory drugs and right ventricular assist devices in severe cases. Prevention of RVF starts with appropriate patient selection for LVAD implant through extensive clinical, echocardiographic and hemodynamic evaluation. Purpose: This study aimed to evaluate the performance of a novel non-invasive echocardiographic method for estimation of right ventricular myocardial work to predict RVF and death after LVAD implant. Methods: Consecutive patients from May 2017 to February 2022 undergoing LVAD implant were retrospectively reviewed. Patients without a useful echocardiographic exam and/or a right heart catheterization prior to LVAD implant were excluded. Myocardial work analysis by Speckle Tracking Echocardiography (STE) was performed in these patients. The primary endpoints were RVF and death. Results: The study included 23 patients (mean age 64±8 years, 91% men). Median follow-up time was 304 days (IQR: 23–1017). GWI significantly correlated with invasively-derived right ventricular stroke work index (RVSWI, r=0.538; p=0.008) and pulmonary arterial compliance (PAC, r=−0.522; p=0.013). Patients who experienced RVF (26.1%) had lower GWI (p=0.047) and GWE (p=0.001) and higher GWW (p=0.001). Patients who experienced death at 30 days after LVAD implant (26.1%) had lower GWE (p=0.005) and higher GWW (p=0.006). Performance for prediction of RVF after LVAD implant was greatest for GWE (AUC 0.92), followed by GWW (AUC 0.88) and GWI (AUC 0.78). A cut-off of 77% for GWE have a 100% sensibility and 82% specificity for prediction of RVF. At long term follow-up, death occurred in 4 patients (29%) in the GWE>77% group and in 6 patients (67%) in the GWE<77% group (hazard ratio for death, 0.24; 95% CI, 0.07 to 0.89, p=0.032). Conclusions: Right ventricular myocardial work is a strong predictor of RVF after LVAD implant and death at long-term follow up. Its calculation should be implemented in the evaluation for LVAD candidacy. Funding Acknowledgement: Type of funding sources: None.